On the similarities and differences of non-traumatic sound exposure during the critical period and in adulthood - Eggermont, Jos J. (Frontiers in Systems Neuroscience, 2013)
There is an almost dogmatic view of the different effects of moderate-level sound stimulation in neonatal vs. adult animals. It is often stated that exposure in neonates results in an expansion of the cortical area that responds to the frequencies present in the sound, being either pure tones or frequency modulated sounds. In contrast, recent findings on stimulating adult animals for a sufficiently long time with similar sounds show a contraction of the cortical region responding to those sounds. In this review I will suggest that most neonatal animal results have been wrongly interpreted (albeit generally not by the original authors) and that the changes caused in the critical period and in adulthood are very similar. Thus, the mechanisms leading to the cortical map changes appear to be similar in the critical period and in adulthood. Despite this similarity, the changes induced in the critical period are generally permanent (unless extensive training paradigms to revert the changes are involved), whereas in adults a slow recovery (months) to pre-exposure conditions takes place.